A Prospective Study of Renal Transplant Recipients: A Fall in Insulin Secretion Underpins Dysglycemia After Renal Transplantation. Issue 11 (November 2016) - Langsford, David; Obeyesekere, Varuni; Vogrin, Sara; Teng, Jessie; MacIsaac, Richard J.; Ward, Glenn; Alford, Frank; Dwyer, Karen M.
Abstract : Background: Dysglycemia (encompassing impaired glucose tolerance and diabetes mellitus) arising after renal transplantation is common and confers a significant cardiovascular mortality risk. Nonetheless, the pathophysiology of posttransplant dysglycemia is not well described. The aim of this study was to prospectively and comprehensively assess glucose handling in renal transplant recipients from before to 12 months after transplantation to determine the underpinning pathophysiology. Materials and Methods: Intravenous and oral glucose tolerance testing was conducted before and at 3 and 12 months posttransplantation. An intravenous glucose tolerance test was also performed on day 7 posttransplantation. We followed up 16 transplant recipients for 3 months and 14 recipients for 12 months. Insulin secretion, resistance and a disposition index (DI (IV)), a measure of β cell responsiveness in the context of prevailing insulin resistance, were also determined. Results: At 12 months, 50% of renal transplant recipients had dysglycemia. Dysglycemia was associated with a dramatic fall in DI (IV) and this loss in β cell function was evident as early as 3 months posttransplantation (23.5 pretransplant; 6.4 at 3 months and 12.2 at 12 months posttransplant). Differences in the β cell response to oral glucose challenge were evident pretransplant in those destined to develop dysglycemia posttransplant (2-hour blood glucose level 5.6 mmol/L versus 6.8 mmol/L; P < 0.01). Conclusions: Dysglycemia after renal transplantation is common, and the loss of insulin secretion is a major contributor. Subclinical differences in glucose handling are evident pretransplant in those destined to develop dysglycemia potentially heralding a susceptible β cell which under the stressors associated with transplantation fails.